Les MOOC : une promesse de rupture non tenue - François Acquatella; Valérie Fernandez; Thomas Houy (Centre National d'Enseignement à Distance, 2022)
« MOOCs represent a tremendous opportunity for positive and radical transformation of the education sector »... this was essentially the most widespread belief around MOOCs when they were popularized in 2012 with the creation and development of the Coursera platform. Ten years later, has the hope raised by this new teaching modality been disappointed or, on the contrary, satisfied? It appears from our observations (Acquatella et al., 2019) and the academic literature that most initiatives to complement or substitute traditional teaching with online courses have remained embryonic and this despite the constraints imposed by the Covid crisis. MOOCs are still struggling to establish formal proof of their value to all the actors involved in the ecosystem - learners, professors and higher education institutions. To date, it seems reasonable to believe that these educational devices have created a promise of disruption that has not been fulfilled.